PENGARUH WAKTU PENYIANGAN TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS SORGUM (Sorgum bicolor (L.) Moench) - Dewi Hiasinta Tarigan; T. Irmansyah T. Irmansyah; Edison Purba (Universitas Sumatera Utara, 2013)
ABSTRACTThis study aims to know the effect of weeding time on the growth and production of some varietiesof sorghum in Pasar 1 street Tanjung Sari, Medan, with ± 25 meters altitude above the sea level inJuly – November 2012. The design use Factorial Separated Design Frame with 2 aspects. The firstaspect as a main frame is variety (Sangkur, Kawali, Numbu) and the second factor as subordinateframe is weeding time (clean weeding during research, weeded after 7 days planting, weeded after 14days planting, weeded after 21 days planting, weeded after 28 days planting, without weedingprocess). The parameters measured were plant height, number of leaves, flowering, canopy wetweight, production per sample, production per plot, the production per ha, the weight of 1000 seeds.From the research, varieties significantly affect on plant height (4-8 weeks after planting), number ofleaves (6 and 8 weeks after planting), flowering, canopy wet weight, production per sample,production per plot, production per hectare, weight 1000 seeds.Weeding time significantly affect onplant height (4-8 weeks after planting) the number of leaves (2-8 weeks after planting), the weight ofthe wet canopy, production per sample, production per plot, production per hectare, the weight of1000 seeds. Interaction significantly affect on the number of leaves 6 weeks after planting.Keywords : sorghum, varieties, and weeding time